2022
DOI: 10.3390/ma15144866
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Aggregate Gradation on the Volumetric Parameters and Rutting Performance of Asphalt Concrete Mixtures

Abstract: The main objective of this study was to determine the effect of aggregate gradation (AG) on the volumetric parameters (VPs) and rutting performance (RP) of asphalt concrete (AC) mixtures. The boundary sieve (BS) between fine and coarse aggregates was 2.36 mm size, and 15 gradation curves of three nominal maximum aggregate sizes (13.2, 19.0, and 26.5 mm) were designed based on the percentage passing of the BS. A vibrating compaction test of coarse aggregates, Marshall compaction and wheel-tracking tests of AC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The coarse aggregate is limestone, the fine aggregate is machine-made sand (0–5 mm), and the filler is limestone powder. Asphalt mixture samples are prepared under the optimum asphalt binder content obtained by the Marshall method [ 21 ]. The aggregate gradation, optimum asphalt binder content, and air-void content of the two asphalt mixtures are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The coarse aggregate is limestone, the fine aggregate is machine-made sand (0–5 mm), and the filler is limestone powder. Asphalt mixture samples are prepared under the optimum asphalt binder content obtained by the Marshall method [ 21 ]. The aggregate gradation, optimum asphalt binder content, and air-void content of the two asphalt mixtures are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Considering that NMPS of the asphalt mixtures used in this study is 13.2 mm, the BSS selected was 2.36 mm. Moreover, if the aggregate particles greater than or equal to 2.36 mm are considered the skeleton of coarse aggregates, AC can also be designed as a skeleton-dense gradation [ 24 ].…”
Section: Family Of Gradation Curves and Gradation Rangementioning
confidence: 99%
“…Previous research indicated that an intrinsic relationship existed between VMA and VCA, the percentage passing of the boundary sieve, the bulk specific gravity of the mineral aggregate, etc. [17,18]. Therefore, studying the VCA of coarse aggregates is fundamental and necessary for the grading design of SMA and HMA.…”
Section: Introductionmentioning
confidence: 99%